Assistance for East Waringin SMEs Go Digital - Rita Kusumawati (Peneliti Teknologi Teknik Indonesia, 2021)
The purpose of this PPM KKN service program is to assist partners in this case 3 MSMEs in the East Waringin area, namely Bakinang coffee shop, Norbisa MSME, Ilinda MSME. The three MSMEs experienced almost the same problems, namely the limited area of product marketing, not yet utilizing digital marketing to promote and market their products. Moreover, the impact of the COVID-19 that hit, caused the demand for products from the three MSMEs to decrease drastically. In addition, business financial records have not been properly administered. To overcome these problems, this program uses the following methods: training, counseling, and mentoring. Activities carried out to overcome these MSME problems include: redesigning product labels, making product catalogs, product packaging, promoting and selling products through digital marketing and marketplaces as well as conducting financial administration training. The results of this service program are: MSMEs have promotion and sales accounts on Instagram, have sales accounts on the Shopee marketplace, more attractive product packaging, and have a product catalog.